Pandangan Hukum Islam Terhadap Implementasi Akad Mudharabah dengan Jasa di Bank Muamalat - Hali Makki (Program Pascasarjana Universitas Ibrahimy, 2019)
According to the study of Islamic law, Bank Muamalat’s services are unlawful because those services require interest and provide an offer for profit sharing. Therefore those services are unlawful because those only make promises. According to some scholars, those like usury. Bank Muamalat should have the legal variables that are binding on the banking laws under Bank Indonesia’s regulations. Islamic law also becomes the main reference in akad mudharabah, so that akad mudharabah does not come out from fiqh scholars thought or does not come out from fiqh studies.